2014
DOI: 10.1063/1.4869456
|View full text |Cite
|
Sign up to set email alerts
|

Angle-independent colorization of copper surfaces by simultaneous generation of picosecond-laser-induced nanostructures and redeposited nanoparticles

Abstract: The simultaneous generation of nanostructures and redeposited nanoparticles on copper surfaces through their direct ablation in air by a high power and high repetition rate ps laser was demonstrated. Basic and detailed analysis on the formation and the size distribution of nanoparticles spreading over the nanostructured copper surfaces was performed. Lower scanning speed causes more laser pulse input onto the target surface, resulting in a more dense distribution of the nanoparticles with a nearly constant mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…Fan et al 2021. used single laser pulses to demonstrate colours on copper, where each colour was associated with a single set of laser parameters.…”
mentioning
confidence: 99%
“…Fan et al 2021. used single laser pulses to demonstrate colours on copper, where each colour was associated with a single set of laser parameters.…”
mentioning
confidence: 99%
“…Metallic nanoparticles (NPs) exhibit unique plasmonic responses when exposed to optical radiation, leading to promising applications in many fields, such as material processing, solar cells, medicine, and plasmon‐assisted photochemistry . It was shown that the surface plasmon (SP) resonance of nanoparticles is influenced by factors such as particle size, shape, and permittivity .…”
Section: Introductionmentioning
confidence: 99%
“…There is particular interest in creating patterns or structures on a surface at the micro-and nano-scale with potential applications in optics, [1][2][3] photonics, 4,5 chemical catalysis, 6,7 optical biosensing, 8,9 materials surface processing, 5,[10][11][12] and so forth. For such a reason, further developments in surface nanostructure generation are of importance for both nanoscience and nanotechnology.…”
Section: Introductionmentioning
confidence: 99%
“…Laser-based methods have been largely exploited in the synthesis of nanostructures, and laser ablation with femtosecond (fs) pulses has been demonstrated as a valuable tool for both fabrication of nanostructured films by deposition of the ablation plume [13][14][15] and direct surface micro-and nano-structuring of solid targets. [1][2][3]5,10 Many of the studies on fs direct laser structuring exploit laser ablation induced by a beam with a Gaussian intensity spatial profile. By varying the characteristics of the laser pulse parameters, fabrication of a large variety of surface structures on metals and semiconductors is achieved, going from controlled randomly distributed nanostructures (cavities, wires, protrusion, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation